A quantitative comparison of wild-type and gatekeeper mutant cdk2 for chemical genetic studies with ATP analogues. - Elphick, L; Lee, SE; Child, E; Prasad, A; Pignocchi, C; Thibaudeau, S; Anderson, A; Bonnac, L; Gouverneur, V; Mann, D (2009)
Chemical genetic studies with enlarged ATP binding sites and unnatural ATP analogues have been applied to protein kinases for characterisation and substrate identification. Although this system is becoming widely used, there are limited data available about the kinetic profile of the modified system. Here we describe a detailed comparison of the wild-type cdk2 and the mutant gatekeeper kinase to assess the relative efficiencies of these kinases with ATP and unnatural ATP analogues. Our data demonstrate that mutation of the kinase alters neither the substrate specificity nor the phosphorylation site specificity. We find comparable K(M)/V(max) values for mutant cdk2 and wild-type kinase. Furthermore, F80G cdk2 is efficiently able to compensate for a defective cdk in a biological setting.